The Interaction Model of Concentrated Solar Radiation with Materials - M. S., Payzullakhanov (Journal of Energy Conservation, 2020)
The paper analyzes approaches to modeling the processes of interaction of concentrated solar radiation with materials. The experimental results obtained on the synthesis of materials from a melt in a solar furnace are presented. The features of the interaction of concentrated solar radiation with materials are analyzed. The mechanisms are described and a model for the interaction of concentrated solar radiation with materials is created. A feasibility study is proposed for the technology of glass-based glass materials obtained on the Big Solar Furnace.
Keywords: solar furnace; melts; synthesis; structures; hardening; microstructure; fine grain.